2013
DOI: 10.1007/s00253-013-5243-9
|View full text |Cite
|
Sign up to set email alerts
|

Odorant binding proteins: a biotechnological tool for odour control

Abstract: The application of an odorant binding protein for odour control and fragrance delayed release from a textile surface was first explored in this work. Pig OBP-1 gene was cloned and expressed in Escherichia coli, and the purified protein was biochemically characterized. The IC₅₀ values (concentrations of competitor that caused a decay of fluorescence to half-maximal intensity) were determined for four distinct fragrances, namely, citronellol, benzyl benzoate, citronellyl valerate and ethyl valerate. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 31 publications
1
42
0
1
Order By: Relevance
“…38 Most of the studies regarding lepidopteran OBPs have focused on Noctuidae species, whereas OBP members from other families are relatively scarce. 39,40 In the present study, the full lengths of two GOBP cDNAs have been identified from the antennae of C. sinensis using RT-PCR and RACE techniques; these are the first GOBPs in the family Gracillariidae to date, and they enrich the base data for further structural, functional and evolutional studies of OBPs in Lepidoptera.…”
Section: Discussionmentioning
confidence: 89%
“…38 Most of the studies regarding lepidopteran OBPs have focused on Noctuidae species, whereas OBP members from other families are relatively scarce. 39,40 In the present study, the full lengths of two GOBP cDNAs have been identified from the antennae of C. sinensis using RT-PCR and RACE techniques; these are the first GOBPs in the family Gracillariidae to date, and they enrich the base data for further structural, functional and evolutional studies of OBPs in Lepidoptera.…”
Section: Discussionmentioning
confidence: 89%
“…In Ae. aegypti, these proteins were not investigated for their function, but it has been suggested that they might be involved in eggshell formation (Costa-da- Silva et al, 2013;Marinotti et al, 2014). In An.…”
Section: (3) Regeneration and Developmentmentioning
confidence: 99%
“…A single report has been published on the use of a mammalian OBP in a filtering trap for the herbicide atrazine (Bianchi et al, 2013). Another interesting application of OBPs for removing unpleasant odours has been proposed by Silva et al (2013), who incorporated the pig OBP on fabrics for clothes. The immobilized protein served a dual purpose, removing or reducing cigarette odour and slowly releasing pleasant fragrances previously bound to the OBP.…”
Section: Technological Applicationsmentioning
confidence: 99%
“…18 Silva et al explored, for the first time, the use of pig OBP-I to functionalize cotton fabrics, by electrostatic affinity, for the release of fragrances and the reduction of unpleasant odors, like cigarette smoke. 19 In this work, we explored two strategies for the release of βcitronellol from cotton functionalized with CBM-based fusion proteins. In the first strategy, pig OBP-I from Sus scrofa was fused with the CBM N 1 from Cellulomonas f imi (OBP::GQ 20 ::CBM) and incubated with the fragrance prior to cotton functionalization.…”
Section: Introductionmentioning
confidence: 99%